Advancing Theatre Costume and Makeup As Agents Of Cultural Transmission And Rejuvenation In Duroladipo's O?bakò So (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
Culture is a poly-scenic word with diverse definitive connotations. But generally speaking the idea of culture can be regarded as the sum total of ways of living built up by a group of human beings overtime and transmitted from one generation to another. Hence, culture can be considered to be a dynamic phenomenon that is open to influences from different societies of the world while reinventing itself from time to time, in this wise, the inherent values, norms beliefs, philosophies and religions practices that are peculiar to the cultural reading of a particular society could be acculturated, bastardized or shortchanged by another more influential society leading to partial neglect or total extinction of such cultural heritage in the affected societies, in view of this, this paper adopted analytical, historical and descriptive methods through primary and secondary data to highlight the role of theatre as agent of change and cultural transmission in the Nigerian society while exploring fundamentally the functional capabilities of the craft of costume and make-up in artistically and aesthetically showcasing, interpreting and propagating the Yoruba cultural heritage as evidenced in the production of Duro Ladipo's Oba Koso to the audience in order to project, promote and sustain the rich cultural heritage and values of the Nigerian people in Nigeria and across the world for socio-cultural and economic benefits of all and sundry.
Keywords: Culture; Costume; Make-up; Transmission; Rejuvenation